Efektifitas Problem Based Learning Dengan Alat Evaluasi Quizizz Pada Mata Pelajaran Informatika - Dewa Ayu R. Ratih Dewi; Dian Novian; Roviana H. Dai; Abd. Aziz Bouty; Nikmasari Pakaya (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to determine the effectiveness of implementing the Problem-Based Learning (PBL) model assisted by Quizizz in improving students’ learning outcomes in Informatics, particularly on the topic of data sources, among tenth-grade students at SMA Negeri 2 Paguyaman. The study employed a quantitative approach with an effectiveness research design using a pre-experimental method in the form of a one-group pretest-posttest design. The research subjects consisted of tenth-grade students of SMA Negeri 2 Paguyaman. Data were collected through observation, interviews, documentation, and learning achievement tests in the form of pre-tests and post-tests administered using the Quizizz platform. The data were analyzed using descriptive quantitative statistics, including the calculation of mastery percentages and N-Gain scores. The results indicated that the average student learning outcomes increased from 68% in the pre-test to 79% in the post-test. The N-Gain score of 0.4 was categorized as moderate, indicating that the implementation of Problem-Based Learning assisted by Quizizz was moderately effective in enhancing students’ learning outcomes in Informatics. Furthermore, the use of Quizizz as a digital assessment tool contributed to a more interactive and engaging evaluation process while providing immediate feedback to students. These findings suggest that integrating Problem-Based Learning with digital learning platforms such as Quizizz can effectively support student learning and improve academic achievement.